Investigating the concept of chemical functionalization in forensic applications among pharmacy students: A questionnaire study - Khalid W. Zainulabdeen; Alaa A. Rashad; Shams A. Ismeal; Muna Bufaroosha; Shaimaa A. Hussein; Omar Al-Tameemi; Ziad Fidil; Wedad H. Al-Dahhan; Rahimi M. Yusop; Emad Yousif (Universitas Negeri Yogyakarta, 2025)
Forensic science plays a crucial role in the criminal justice system by providing essential evidence and aiding the resolution of crimes. One significant aspect of forensic science is functionalizing pharmacology, which involves the analysis of drugs and their metabolites in biological samples to ascertain their origins and potential effects. It is imperative for future healthcare professionals, particularly pharmacy students, to gain a comprehensive understanding of the functionalization of pharmacology in forensic science. However, there is a paucity of research on pharmacy students' current knowledge and comprehension in this specific domain. Hence, the present study aimed to utilize a questionnaire-based approach to explore pharmacy students' understanding of functionalizing pharmacology in forensic science. The primary objective of this investigation was to identify strengths and weaknesses within this cohort's knowledge base, ultimately offering recommendations for enhancing pharmacy education in this field.